Care needs of children with disabilities - Use of the Pediatric Evaluation of Disability Inventory - Fernanda Moreira Teles; Rosa Resegue; Rosana Fiorini Puccini
Abstract Objective: To describe the care needs reported by caregivers of children with disabilities going through the school inclusion process using the Pediatric Evaluation of Disability Inventory. Methods: Cross-sectional study with 181 children aged 7-10 years with physical or mental disabilities, undergoing the inclusion process in elementary school in 2007. Location: 31 schools of the Regional Education Board-District of Penha, East Side the city of São Paulo. The children's care needs according to the caregivers were assessed in three areas-self-care, mobility and social function, using the Pediatric Evaluation of Disability Inventory, according to the following score: 5, Independent; 4, Supervision; 3, Minimum Assistance; 2, Moderate Assistance; 1, Maximum Assistance and 0, Total Assistance. For statistical analysis, we used Student's t-test and analysis of variance (ANOVA), with p<0.05 being statistically significant. Results: The lower means, with statistically significant differences, were observed for the items related to social function (55.8-72.0), followed by self-care functions (56.0-96.5); for all types of disabilities, except for children with physical disabilities, who had lower means for self-care (56.0) and mobility (63.8). Conclusions: Social function was the area referred to as the one that needed a higher degree of assistance from the caregiver and the Pediatric Evaluation of Disability Inventory is a tool that can help identify these needs and develop a more targeted intervention.